International Financial Statistics Yearbook, 2016. (International Financial Statistics; International Financial Statistics ;, 2016)
This 2016 yearbook issue of International Financial Statistics is a standard source of statistics on all aspects of international and domestic finance. The monthly printed issue of IFS reports current monthly, quarterly, and annual data, while the yearbook reports 12 observations of annual data. Most annual data on the CD-ROM and Internet begin in 1948; quarterly and monthly data generally begin in 1957; most balance-of-payments data begin in 1970. The notes to the country tables in the monthly issues provide information about exceptions in the choice of the consumer price index (generally line 64) and the period average exchange rate index. Quotas are reviewed at intervals of not more than five years. The reviews take account of changes in the relative economic positions of members and the growth of the world economy. The General Resources Account resources consist of the currencies of Fund member countries, SDRs, and gold.